Selection and identification of Pseudomonas and Bacillus Rhizobacteria with Bioinoculant potential for Sorghum - Befekadu Teshome; Eleni Belay; Barkelegne Mengesha; Zerihun Tsegaye; Edwin K. Akley; Awuku Frederick (International Journal of Science, Technology, Engineering and Mathematics, 2025)
This study aimed to select and identify elite strains of plant growth-promoting rhizobacteria (PGPR) among phosphate-solubilizing bacteria (PSB) conserved at the Ethiopian Biodiversity Institute. In-vitro screening for plant growth-promoting traits and abiotic stress tolerance identified 12 promising PGPR isolates. These strains exhibited phosphate solubilization (index 1.8–3.2), auxin production, nitrogen fixation, and ammonia production. All isolates showed drought tolerance, and some exhibited salt tolerance (up to 10% NaCl). 16S rDNA sequencing identified Pseudomonas frederiksbergensis, Pseudomonas fluorescens, Pseudomonas rhodesiae, Pseudomonas azotoformans, and Bacillus altitudinis. These strains have strong potential as bioinoculants for sustainable sorghum cultivation. Future greenhouse and field trials are recommended to validate their effectiveness.